ANALYSIS OF THE CRIMINAL SYSTEM OF THE PRACTICE OF PERSECUTION IN THE CRIMINAL OF THEFT IN THE JURISDICTION OF THE ASMAT RESORT POLICE - Semy B.A Latunussa (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2023)
This study aims to determine the punishment system for perpetrators of persecution of perpetrators of criminal acts of theft in the Legal Area of the Asmat Resort Police and to determine the obstacles to law enforcement against perpetrators of practicing persecution of perpetrators of criminal acts of theft in the Legal Area of the Asmat Resort Police. The author analyzes the data using the socio-juridical approach method, that is, in addition to studying law theoretically and normatively in the form of analyzing various laws and regulations, books and articles that have a correlation and are relevant to the problems studied, will also examine the law in its implementation using techniques data collection through interviews and documentation. The criminal system and punishment that can be applied to perpetrators of persecution of perpetrators of criminal acts of theft is only limited to perpetrators of persecution who actually act as movers and provocateurs who influence the practice of persecution for members of the public at the place where the perpetrators of theft were caught, by imposing Article 170 Paragraph (3) and Article 351 of the Criminal Code, if the persecution is carried out until the perpetrator of the theft dies, while other residents who carry out the persecution are not harmed. The obstacles to law enforcement for the perpetrators of the persecution of the perpetrators of the crime of theft include the lack of Investigation Unit personnel and members of the Asmat Police, the absence of operational car facilities that can carry the perpetrators of persecution because there are no cars that can operate in the Asmat Regency area, the lack of members' legal knowledge, and the absence of a district attorney's office or a district court in Asmat District, which made it difficult for the perpetrators of persecution to be detained.